Thermomigration and Soret effect in NaxCoO2 as thermoelectric material: Preparation and characterization of sodium cobaltate thin films. Issue 5 (20th December 2015) - Schneider, Christian; Schichtel, Patrick; Mogwitz, Boris; Straubinger, Rainer; Beyer, Andreas; Rohnke, Marcus; Volz, Kerstin; Janek, Jürgen
Abstract : Sodium cobaltate (Na x CoO2, NCO) is a model type thermoelectric material for high temperature applications, which is representative for the class of non‐stoichiometric and mixed ion‐electron conducting thermoelectrics (e.g., Cu2 –  x Se). The present study deals with the kinetic instability of the originally homogeneous chemical composition when a temperature gradient is applied – a common situation in thermoelectric materials with a mobile component (element), but rarely considered in thermoelectric materials research so far. In order to investigate a well reproducible system, highly epitaxial thin films of Na x CoO2 with an atmosphere protective capping layer of alumina are prepared via pulsed laser deposition on sapphire (001) and lanthanum aluminate (111). A self‐designed non‐isothermal set‐up allows the precise determination of the heat of transport for mobile sodium as 8.3 kJ mol −1 and, therefore, the quantification of thermodiffusion (i.e., the Ludwig‐Soret effect in the stationary state). The experiments also allow to estimate the chemical diffusion coefficient of sodium at 422 K as about D ˜ N a  = 5 × 10 −4  cm 2  s −1 .